Fabrication of p-type 2D single-crystalline transistor arrays with Fermi-level-tuned van der Waals semimetal electrodes - Seunguk Song; Aram Yoon; Sora Jang; Jason Lynch; Jihoon Yang; Juwon Han; Myeonggi Choe; Young Ho Jin; Cindy Yueli Chen; Yeryun Cheon; Jinsung Kwak; Changwook Jeong; et al. (Nature Communications, 2023)
Abstract High-performance p-type two-dimensional (2D) transistors are fundamental for 2D nanoelectronics. However, the lack of a reliable method for creating high-quality, large-scale p-type 2D semiconductors and a suitable metallization process represents important challenges that need to be addressed for future developments of the field. Here, we report the fabrication of scalable p-type 2D single-crystalline 2H-MoTe2 transistor arrays with Fermi-level-tuned 1T’-phase semimetal contact electrodes. By transforming polycrystalline 1T’-MoTe2 to 2H polymorph via abnormal grain growth, we fabricated 4-inch 2H-MoTe2 wafers with ultra-large single-crystalline domains and spatially-controlled single-crystalline arrays at a low temperature (~500 °C). Furthermore, we demonstrate on-chip transistors by lithographic patterning and layer-by-layer integration of 1T’ semimetals and 2H semiconductors. Work function modulation of 1T’-MoTe2 electrodes was achieved by depositing 3D metal (Au) pads, resulting in minimal contact resistance (~0.7 kΩ·μm) and near-zero Schottky barrier height (~14 meV) of the junction interface, and leading to high on-state current (~7.8 μA/μm) and on/off current ratio (~105) in the 2H-MoTe2 transistors.